Pendampingan Pembuatan Soal Ujian HOTS berbasis Komputer dengan Aplikasi TCEXAM bagi Guru di MI Raudlatul Ulum dengan Metode LFA - M. Iqbal Tawakkal; Sunu Wahyudhi; Auliyaur Rokhim; Marika Putri Pratama; Moh. Rouf Ainurrokhim Ainurrokhim; Devi Putri Ayu (I-Com: Indonesian Community Journal, 2024)
The advancement of ICT is currently having a positive impact on education. This can be seen from the growing development of computer technology used by the educational unit level. Implementation of Daily Deuteronomy, Mid-Semester Examination, and Final Semester Examination at MI Raudlatul Ulum so far uses paper-based exams. The solution offered to overcome the problem is to provide assistance and training in Making Computer-Based Examination Questions with the TCExam Application. The method used in this service is the Logical Framework Approach (LFA). The activities carried out in this service consist of two steps, namely the preparation step and the implementation step. The final result of the community service activities in the form of assistance in the implementation of the End of Semester Examination at MI Raudlatul Ulum has so far used paper-based exams to turn into an online exam system based on the TCExam Application. This community service activity must be continued to the stage of continuous assistance to maintain the quality of HOTS questions made by partners and to analyze the level of difficulty of the items.